All Eyes on Papua: Deforestation of Indigenous Forests - Wibawa, Firmansyah Wisnu Murti; Handayani, Sri Wahyu (Jurnal Idea Hukum, 2024)
Every development impacts environmental changes, especially the exploitation of forest resources in managing and utilizing forest products, which affects these changes. In other words, exploitation of forest resources is a form of forest destruction. The Awyu Tribe indigenous community, accompanied by the Coalition to Save Papua Traditional Forests, is suing for an environmental permit for PT Indo Asiana Lestari (PT IAL) oil palm plantations. The indigenous people of West Papua firmly reject the plan to clear 36 thousand hectares of forest. If the project is implemented, the traditional forest, their livelihood source, will be lost, and their lives will be threatened. This research method uses a normative legal research approach. Who will search for, collect, and analyze qualitative, primary, and secondary legal materials with the aim of legal practice in the context of legal problem-solving? This approach has prescriptive characteristics, which assess what is right or wrong, appropriate or inappropriate. For the results of this research, a structured and careful framework is needed to handle this conflict. Therefore, the steps taken in conflict resolution must be wise and fair. In addition, conflict resolution policies must be able to take into account the aspirations and interests of local indigenous communities.Keywords: Customary forests; Environmental Permits; Indigenous communities